Audit Quality and Its Influence on Stakeholder Trust: A Qualitative Analysis - Surya, Dika; Pratiwi, Eka; Wijaya, Galang; Permadi, Hani; Suryani, Ina (Manunggal Halim Jaya, 2021)
This qualitative study aims to explore the intricate relationship between audit quality and stakeholder trust in financial reporting. Through in-depth interviews with auditors, investors, regulators, and corporate executives, insights were gathered regarding perceptions, experiences, and expectations concerning audit quality and its influence on stakeholder trust. Thematic analysis revealed key dimensions of audit quality, including auditor independence, competence, objectivity, adherence to professional standards, and perceptions of audit effectiveness. Stakeholders emphasized the importance of transparent disclosure practices, accountability in corporate governance, credibility of auditors and financial statements, and regulatory oversight in fostering trust in financial reporting. The findings underscored the pivotal role of regulatory bodies, such as the PCAOB and SEC, in promoting audit quality, deterring fraudulent behavior, ensuring auditor accountability, and maintaining market confidence. Overall, the study contributes to a deeper understanding of the mechanisms shaping stakeholders' perceptions of audit quality and trust in financial reporting, with implications for market efficiency, investor protection, and corporate governance.